Análise do processo de torneamento a quente auxiliado por resistência elétrica de quartzo - Spinelli Júnior, Adhemar José [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
Um dos principais objetivos da indústria metal-mecânica é o aumento da produtividade nos processos de usinagem, o que pode ser conseguido por meio de maiores taxas de remoção de material. Este requisito está associado ao desgaste da ferramenta de corte, uma vez que a redução de sua vida acarreta aumento dos custos de fabricação, não só pelo valor unitário da ferramenta, mas também pelo tempo consumido na indesejável interrupção da operação. Atualmente, um dos importantes caminhos para o aumento da vida da ferramenta aponta para o desenvolvimento de materiais mais resistentes ao desgaste, como as pastilhas de nitreto cúbico de boro policristalino (PCBN). No entanto, o custo unitário destas ferramentas é consideravelmente alto...

One of the main of the metalworking industry is the increase of productivity in machining processes, which can be obtained through larger material removal rates. This requirement is associated to be cutting tool wear evolution, since the reduction of tool life increases the production costs, not only for unitary value of the tool, but also for the time consumed in the undesirable interruption of the operation. Nowadays, an important way to increase tool life is the development of more wear resistant materials, such as polycrystalline cubic boron nitride (PCBN) cutting tools. However, the unitary cost of these tools is considerably high, about 10 to 20 times more expensive that coated carbide tools. In addition its best performance occurs at high-speed machining, that demands modern machine tools. Many researchers have been using the technique of heating a workpiece layer immediately before its removal by the cutting tool in order to reduce the shear stress and to improve... (Complete abstract click electronic access below)
Keywords: Usinagem; Metais - Corte; Quartzo; Hot turning; Cutting temperature; Quartz electric resistance